Assessing Immigrant Niches Across Large American Metropolitan Areas. Issue 2 (13th January 2014) - Christopher, S. Carter; Leslie, Timothy F.
Abstract: Previous research into immigrant niche formation has largely focused on immigrant niches in individual urban areas, whereas little attention has been paid to the variation in immigrant group niche formation across urban areas. We investigate niche formation across 26 US metropolitan areas. We introduce the Niche Index as a measure of the propensity of an immigrant group to niche, test whether this is consistent across metro areas, and statistically identify the drivers of niching propensity. We find immigrant niches to be largely located in a limited number of industries and that these niche industries are very consistent within‐group across space. Immigrant groups have significantly higher propensity to niche than New York and Los Angeles in 10 of our 26 cities. We also find that both metropolitan population and immigrant group populations have a significant influence on propensity to niche, as well as a metropolitan area's change in unemployment and the English proficiency of the immigrant group. Copyright © 2014 John Wiley & Sons, Ltd.